STUDY ON APPLICATION OF DRAG-REDUCING TRIMETHYLOLETHANE SLURRY IN DISTRICR COOLING SYSTEM - Indartono, Yuli Setyo; Usui, Hiromoto; Suzuki, Hiroshi; Komoda, Yoshiyuki (Mesin, 2008)
Trimethylolethane (TME) trihydrate slurry is a proper phase-change material for latent heat transportation in cooling systems since it has excellence heat transfer performance and high thermal capacity. Additives, oleyl bishydroxyethyl methyl ammonium chloride (as surfactant) and sodium salicylate (as counter-ion), were used as drag-reducer substance. These additives not only induce drag reduction in TME slurry, but also control particle growth and agglomeration. In this study, energy saving estimation of drag-reducing TME slurry application in district cooling system is invesitgated. It is found that drag-reducing TME slurry gives remarkable pumping power suppresion in the district cooling system. To maintain high performance of heat exchangers, heat transfer enhancement technique may be needed in those exchangers.